2019
DOI: 10.3390/molecules24122245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Zn-Salphen Building Block and Its Acrylic Terpolymer Counterparts as Tunable Supramolecular Recognition Systems

Abstract: In this work, we present the synthesis of a novel Zn-Salphen complex containing an allyl group, which was used as building block in the further preparation of a new family of functional terpolymers. These polymers were obtained through radical co-polymerization with methyl metacrylate (MMA) and n-butyl acrylate (nBuA) in different ratios. The supramolecular recognition behavior of each polymer was evaluated via potentiometric measurements against selected anions in aqueous media. Interestingly, this proof of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 40 publications
(41 reference statements)
1
20
1
Order By: Relevance
“…In our previous work, [29] we found that similar counterparts at 0 % of Salphen component ( i. e . only the acrylic backbone n BuA:MMA at 80 : 20 in mass) yielded also one T g , but such transition occurred at −28.6 °C, a lower temperature if compared to the values in the present study.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…In our previous work, [29] we found that similar counterparts at 0 % of Salphen component ( i. e . only the acrylic backbone n BuA:MMA at 80 : 20 in mass) yielded also one T g , but such transition occurred at −28.6 °C, a lower temperature if compared to the values in the present study.…”
Section: Resultssupporting
confidence: 61%
“…[28] Also, we have shown that unsymmetrical Zn-Salphen derivatives bearing an allyl moiety attached to the aldimine aromatic ring, could efficiently copolymerize together with acrylic monomers n-butyl acrylate (nBuA) and methyl methacrylate (MMA) at different ratios. [29] In those experiments, an nBuA:MMA mass ratio of 80 : 20 exhibited an optimal performance in anion detection and disposable potentiometric sensors. Such ratio maximized the material's anion-discrimination through the polymerized Zn-Salphen binding site, thanks to an enhanced balance in ion permeation inside the polymer phase derived from a favorable internal environment.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations